Clinical study of 3D-printed personalized prostheses for the treatment of traumatic metacarpophalangeal joint defects - Hao Zheng; Yuan Cao; Yunqing Wang; Zhuqing Jia; Yong Liu (BMC Musculoskeletal Disorders)
Abstract Background Complex trauma results in a variety of nonstandard bone defects in the metacarpophalangeal (MCP) joints of patients, limiting the choice of commercial prostheses. This study aims to investigate the early clinical efficacy of 3D-printed personalized prostheses in the reconstruction of traumatic MCP joints. Methods A retrospective analysis was conducted on 7 cases of 3D printed MCP joint prostheses replacement surgeries performed by the same surgeon. We customized the prostheses to the specific trauma scenario based on the patient’s computed tomography (CT) data. We recorded Disabilities of the Arm, Shoulder, and Hand (DASH), Michigan Hand Questionnaire (MHQ) scores preoperatively and at postoperative follow-up. Grip strength, pinch strength, and anterior range of motion (AROM) of the operated hand were investigated at postoperative follow-up. We confirmed the status and complications of the prosthesis based on imaging and clinical evaluation. Standardized response means (SRM) were calculated for each outcome measure. Results All cases were followed up for an average of 28.29 ± 4.03 months. The most significant change in the DASH score occurred from preoperative to one month postoperative, decreasing from 82.58 to 62.21, while the MHQ-Pain score showed the greatest improvement from 76.00 to 37.14. From one to three months postoperative, the MHQ score exhibited the maximum enhancement, rising from 36.90 to 58.67. The AROM increased from 36.00° to 53.71°, and the grip power increased from 6.71 kg to 17.86 kg. The pinch power improved significantly from six to twelve months postoperative (from 1.70 kg to 2.70 kg). Five patients exhibited possibly loose prostheses, while no cases of potential or definitive loosening were observed. All differences in the aforementioned metrics were statistically significant. Conclusion 3D printed prosthetic replacement for traumatic MCP joint defects is effective and feasible, which can achieve personalized treatment and precision medicine and retain sufficient joint motion for patients.